Priorities of Appropriate Intervention to Empowering People with Developmental Disorders and Integrate them into Social Life from the Point of View of their Families - Abuzahera, Amani Obaidullah (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the appropriate intervention priorities to empower people with developmental disorders and integrate them into social life from the point of view of their families. The study population consisted of families of people with developmental disorders (autism spectrum disorder, attention deficit hyperactivity disorder, pervasive developmental disorder) attending the Center for Developmental and Behavioral Disorders at the Children's Hospital in Taif, Saudi Arabia. 275 cases were selected as a random sample from a total of 1096 cases, whether new or previously diagnosed, Saudis and residents, from the beginning of January to the end of March 2023.) autism spectrum disorder 98 cases, and attention-deficit/hyperactivity disorder 53 cases, comprehensive developmental disorders 124 cases). The questionnaire consisted of two main axes:The first axis: early intervention, which includes: a. Preparing and training parents. b. Developing personal skills (safety skills, personal care, table manners).The second axis: integration (inclusion- mainstreaming), and empowerment, which includes: a.Developing communication skills (verbal, non-verbal(. b.Developing social skills (social relations, social interaction). The result of the study concluded that there are challenges facing the families of children with developmental disorders, and the most notable related to anxiety about the future of children in general, and the psychological pressure due to the inability to manage their condition and modify their behavior, which indicates the importance of preparing and training parents as one of the early intervention process. Also, children with developmental disorders need to develop personal skills (safety skills, personal care, table manners). Finally, there are challenges related to communication skills and social skills that could impede the integration and empowerment of children with developmental disorders from the perspective of their families. Consequently, the study came out with a set of recommendations that could serve people with developmental disorders and their families in terms of diagnosis, rehabilitation, integration (inclusion- mainstreaming), and empowerment such as starting an early intervention program, also establishing an educational and rehabilitative club sponsored by the government.
Keywords: Intervention; empowerment; integration (inclusion- mainstreaming); developmental disorders; social life